ESSAYS ON INCOME INEQUALITY AND EDUCATION IN BRAZIL - Joyciane Coelho Vasconcelos (2015)
2012. Applying a methodology proposed decomposition by Fields (2002) was possible to identify the factors that caused the reduction in wage inequality in Brazil on the basis of their main sources of production and reproduction: market imperfections and heterogeneity of workers. The second chapter investigates the minimum wage contribution (SM) for the devolution process of the income of farm work (permanent and temporary) in the period 2002-2012. The microdata used are from PNAD. We used the simulation methodology proposed in DiNardo, Fortin and Lemieux (1996) from the estimated density functions counterfactual Kernel, with some adjustments. The results revealed that in the specific case of agricultural work, the effect of the minimum wage, while workers' protection mechanism is clear only in the structured segment of the labor market (permanent). Faced with the undeniable importance of education on socioeconomic development, and given the current educational context of Brazil. The third chapter presents the main results of the Programme for International Student Assessment (PISA) 2012 for Brazil and analyzes the difference in the type of school, as it shows that students studying in private schools are outperforming those of public schools. It is estimated a school production function by the method of ordinary least squares (OLS) and quantile regression (RLS), in addition to providing a more complete analysis conditional distribution of the test notes. The results revealed that when it comes to explaining inequality in educational performance, differences in socioeconomic conditions far outweigh the differences in school resources.